Analisis Gangguan Berbahasa Keterlambatan Berbicara (Speech Delay) Pada Anak Berusia 6 Tahun - Ramdhina Puteri Amanda; Rika Aulia (LPPM Politeknik Pratama, 2024)
From infant stages to childhood, children's language acquisition and development can be trained. The parental involvement in the acquisition and development of children's language is critical, particularly in the avoidance of language disorders in children. The goal of this research is to determine the acquisition process of language in a six-year-old child with a speech delay disorder. Furthermore, researchers aim to determine the role of parents, family, and the local environment in the language acquisition process that occurs in these children. The descriptive qualitative method was used in this study. The following data collection methods were used: literature review, observation, and personal interview. The primary sources used in this study were children aged six years old who had speech delays, and the secondary sources were e-books, books, and journal or articles related to speech delay problems. The findings of this study show that parents, family, and the surroundings really do have a massive effect on children's language acquisition and development. Speech disorders in children can also be genetically inherited.